Lactococcus lactis As a Versatile Vehicle for Tolerogenic Immunotherapy - Cook, Dana P.; Gysemans, Conny; Mathieu, Chantal (Frontiers in Immunology, 2018)
Genetically modified Lactococcus lactis bacteria have been engineered as a tool to deliver bioactive proteins to mucosal tissues as a means to exert both local and systemic effects. They have an excellent safety profile, the result of years of human consumption in the food industry, as well as a lack of toxicity and immunogenicity. Also, containment strategies have been developed to promote further application as clinical protein-based therapeutics. Here we review technological advancements made to enhanced the potential of Lactococcus lactis as live biofactories and discuss some examples of tolerogenic immunotherapies mediated by mucosal drug delivery via Lactococcus lactis. Additionally, we highlight their use to induce mucosal tolerance by targeted autoantigen delivery to the intestine as an approach to reverse autoimmune type 1 diabetes.